DEVELOPMENT AND CHARACTERIZATION OF NEVIRAPINE LOADED AMORPHOUS SOLID DISPERSIONS FOR SOLUBILITY ENHANCEMENT - GAGANDEEP SINGH; NAVJOT SINGH; RANDEEP KUMAR; NEENA BEDI (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present study entails the development of nevirapine (NVP)-loaded solid dispersions for improvement of solubility and in vitro profile. Methods: Solid dispersions were prepared through blending with a hydrophilic polymer and Vitamin E tocopherol polyethylene glycol succinate (TPGS) using the solvent evaporation method. The optimized formulations were characterized by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction, and morphological investigations by scanning electron microscopy. The optimized formulation was converted into fast dissolving tablets (FDTs) through direct compression technique and was characterized for pre- and post-compression parameters. Both amorphous dispersions and FDTs were evaluated for in vitro drug release. Results: NVP showed pH-dependent solubility in different pH media. Above 0.002% w/v Vitamin E TPGS, a linear relationship was observed between the NVP solubility and Vitamin E TPGS concentration. According to the study, the most suitable formulation was NVP:Vitamin E TPGS (1:0.75) in 30 ml solvent with a drug release of 82.96% in 2 h. The analysis of dissolution data of optimized formulation indicated the best fitting with the Higuchi model. FDTs exhibited faster drug release of about 50% in 5 min indicating desired attributes for the immediate dosage form. Conclusion: The present study vouches for better in vitro profile of NVP from solid dispersion based FDTs.